Immunotherapy of Brain Cancers: The Past, the Present, and Future Directions - Lisheng Ge; Neil Hoa; Daniela A. Bota; Josephine Natividad; Andrew Howat; Martin R. Jadus (Clinical and Developmental Immunology)
Treatment of brain cancers, especially high grade gliomas (WHO stage III and IV) is slowly making progress, but not as fast as medical researchers and the patients would like. Immunotherapy offers the opportunity to allow the patient's own immune system a chance to help eliminate the cancer. Immunotherapy's strength is that it efficiently treats relatively small tumors in experimental animal models. For some patients, immunotherapy has worked for them while not showing long-term toxicity. In this paper, we will trace the history of immunotherapy for brain cancers. We will also highlight some of the possible directions that this field may be taking in the immediate future for improving this therapeutic option.